Decision Making Using Hierarchical Analytical Processes to Evaluate Computer Management Performance - Ajif Yunizar Pratama Yusuf; Kusdarnowo Hantoro; Suryani, Rani (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2022)
The presence of PC computers since the 80s with its rapid and very widespread growth can be seen as a one of the most significant developments in the field of information and communication technology. This study aims to propose decision making using the Analytical Hierarchy Process approach to evaluate computer computers with respect to using the order of preference of the user. To get the most desirable features that affect the decision to choose a computer to be identified. This is realized through a survey conducted on the target group, experienced experts in the telecommunications sector and literature study. The AHP methodwas then used in the evaluation procedure. Analytical Hierarchy Process (AHP) was applied to determine the relative weight of the evaluation criteria applied to rank computer alternatives. The results of this case study illustrate the effectiveness of the proposed computer management performance selection.